(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
The article examines the specific features of the system of images in L. N. Tolstoy’s novella «Hadji Murat». Particular attention is given to the image of Hadji Murat as a “liminal” hero who finds himself caught between two forces and compelled to act within a political trap. The study also considers the role of landscape and material details as active meaningmaking elements, including the symbolism of the frame composition (the thistle motif), which intensifies the tragic ending